Treatment Of Maize Seeds Using An Ultraviolet Irradiation Device (Texas Journal of Engineering and Technology, 2026)
The article presents the results of studies on the technological parameters of an electrotechnological device used for pre-sowing ultraviolet treatment of maize seeds, as well as the optimal processing parameters for electrical stimulation and their relationship with crop yield indicators.